Can Diaphragm Dysfunction Be Reliably Evaluated with Pocket-Sized Ultrasound Devices in Intensive Care Unit? - Gul Gursel; Kamil Inci; Zenfira Alasgarova (Critical Care Research and Practice)
Background. Diaphragm dysfunction (DD) is frequently seen in critically ill patients, and ultrasound could be a useful tool to detect it and to predict extubation success or failure in mechanically ventilated patients. Besides, it would also be useful in differential diagnosis of dyspnea and respiratory failure. The aim of this study is to evaluate usefulness and accuracy of pocket-sized ultrasound devices (PSDs) in assessment of DD in intensive care unit (ICU) patients in comparison with standard ultrasound devices (SD). Methods. In this prospective observational study, we compared the performance of PSD and SD in visualization of diaphragm, detection of paradoxical movement, measurement of tidal and maximal thickness, tidal and maximal excursion, and calculation of thickening fraction (TF) of the diaphragm. We used Bland and Altman test for agreement and bias analysis and intraclass correlation analysis to evaluate interobserver variability. Results. Thirty-nine patients were included in the study. In 93% of the patients, diaphragm was visualized with PSD. There was very good agreement between the measurements of the devices, and there was no proportional bias in the measurements of tidal inspiratory and expiratory thickness, tidal TF, tidal excursion, and maximal inspiratory thickness. In interobserver reliability analysis of all measurements for both devices, ICC coefficients were higher than 0.8. Total diaphragm examination times of the devices were similar (p>0.05). Conclusion. These results suggest that PSD can be useful in ICU patients for evaluating DD. But further studies are required to determine the exact place of these devices in evaluation of DD in ICU patients.